H‐Mediated Magnetic Interactions between Layers in a 2D MnII–Dicyanamide Polymer: Neutron Diffraction, DFT, and Quantum Monte Carlo Calculations. Issue 3 (22nd November 2017) - Gillon, Béatrice; Hammerschmied, Albert; Gukasov, Arsen; Cousson, Alain; Cauchy, Thomas; Ruiz, Eliseo; Schlueter, John A.; Manson, Jamie L.
Abstract : We report neutron‐diffraction investigations of the quasi‐2D Mn II (dca)2 (pym)(H2 O) (pym = N2 C4 H4 ) compound, where high‐spin Mn II ions are bridged by dicyanamide anions, [N(CN)2 ] – (herein abbreviated dca). Inside the layers, Mn 2+ ions are connected by single or double dca bridges. The magnetic phase diagram was established by neutron diffraction on a single crystal. In the low‐field phase, the Mn II ions are antiferromagnetically ordered in the layers, with moments nearly parallel to the c axis, and the layers are antiferromagnetically coupled. The spin‐flop phase corresponds to ferromagnetic coupling between the antiferromagnetic layers, in which the Mn II moments are nearly perpendicular to the c axis. The induced spin‐density distribution in the paramagnetic phase, determined by polarized neutron diffraction, visualizes the superexchange pathways through the dca ligands within the layers and through H bonding between neighboring layers. The theoretical spin density obtained by bidimensional periodic DFT calculations is compared with the experimental results. Furthermore, quantum Monte Carlo simulations have been performed to compare the DFT results with experimental susceptibility measurements. Abstract : The magnetic phase diagram of Mn II (dca)2 (pym)(H2 O) is established by neutron diffraction. The magnetic‐interaction pathways are visualized by the PND induced‐spin distribution in the paramagnetic phase. Antiferromagnetic coupling is mediated by dca bridges inside layers and by H bonding between layers. DFT and QMC calculations are compared with PND results and SQUID susceptibility measurements.